E-Knowledge Module Development with Sprint Method in Dr. Ramelan Navy Hospital - Caecilia Indarti; Siti Saerah; Djazuli Chalidiyanto (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2022)
Background: Hospitals need to manage document systems well. Dr Ramelan Navy hospital only 15% of the training materials have been documented. Knowledge of basic infection control programs only reached 57.2% and effective communication reached 56%. Objective: The purpose of this study is to analyze the factors causing the documentation of training materials under the standard, to determine solutions to improve the documentation of training materials to reach the standard and to develop an activity plan in overcoming the problem of documentation of training materials that have not reached the standard. Methods: This study uses the analytical observational method. The method used is the Problem Solving Cycle (PSC) approach. Data obtained through interviews, observations, and documentation in several departments and work units, then processed through a number of stages in overcoming the problem of documentation of training materials. Problems are solved by using a problem solving cycle approach with five stages of problem analysis, strategy design, development strategy, implementation, monitoring, evaluation and feedback. Solution of problems with the development of knowledge modules in hospital management information system. Results: The results at the strategy development stage of the development of the module named E-Knowledge was developed using the Sprint method with five stages of map, sketch, divide, prototype and test. Conclusion: E Knowledge increase knowledge and improve personnel performance.